Political Education the Young Generation Increases Political Participation: Collaboration Educational Institutions and the KIP - Roni Hidayat; Benni Erick; Budi Handoyo (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study examines political education in increasing the political participation of the younger generation through collaboration between educational institutions and the West Aceh KIP. The study used a qualitative approach to analyze the research results. The informants who served as the main source of information were ten people consisting of three members of the West Aceh KIP, five teachers of SMAN and two lecturers of STAIN Teungku Dirundeng Meulaboh. The selection of informants for this study was based on considerations of the competency of the informants in providing the research data information needed by the researcher. This study was conducted for three months. Data collection techniques used interview and documentation techniques. To analyze the findings in the field using triangulation techniques. The results of the field study indicate that collaboration between educational institutions and the West Aceh KIP can increase political participation through political education for the younger generation in West Aceh Regency through a collaborative program between educational institutions and the KIP. Conclusion The collaborative program between KIP and educational institutions in increasing political participation through political education for the young generation of West Aceh is a new breakthrough in providing political education. This activity is also very effective in providing political understanding to the young generation and can increase their participation in political events in West Aceh Regency. Therefore, this program is very good and can be adopted by related institutions in providing political education in a broader context.